Talim Bay Marine Conservation & Ecotourism Center - Benavidez, Grace Ann L.; Madrid, Dolores Cecilia T. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
The Talim Bay Marine Conservation and Ecotourism Center in Lian, Batangas is a project that aims to initiate and regulate tourism in the municipality, while prioritizing the preservation and conservation of its ecosystem from ridge to reef. It also aims to prevent the possible deterioration of Talim Bay due to the predicted influx of tourism and development in the next few years, learning from the previous predicament of its neighboring coastal area, Matabungkay Beach. The proposed design project is a development that aims to bring together the concerned stakeholders of the municipality, namely the local government, the academe, the locals and the tourists, designing a space where they can interact and work together towards the proper management of the natural environment. The development consists mainly of a tourist/visitor center, an eco-resort and a research center, following the concept of the Information, Education and Communication (IEC) method implemented in the municipality's Integrated Coastal Management Plan (ICMP). The development also includes necessary support facilities as part of its sustainable and self-sustaining nature. This study contains researches and design solutions used by the proponent to answer the various issues in designing this type of development.
Includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Marine resources conservation; Ecotourism center; Marine ecotourism facilities -- Lian (Batangas).